Speech Acts, Politeness, and Pragmatic Failures in Intercultural Contexts - Kasim, Nuraeni; Sueb (Indonesian Scientific Publication, 2024)
Pragmatics plays a fundamental role in mediating meaning and facilitating effective communication across cultural boundaries. This narrative review aims to examine the role of pragmatic competence in intercultural communication by synthesizing theoretical and empirical evidence from diverse contexts. Literature was systematically collected from databases including Scopus, PubMed, and Google Scholar using keywords such as “intercultural pragmatics,” “speech acts,” and “pragmatic competence.” Studies were included based on relevance, methodological rigor, and empirical contribution, encompassing research from educational, professional, and societal settings. The results highlight five key themes: speech acts and politeness strategies, pragmatic failures and communication barriers, technology in pragmatic learning, cultural and religious pragmatics, and teacher and curriculum integration. Findings reveal that pragmatic competence is culturally contingent, with speech acts and politeness norms varying widely across societies. Pragmatic failures are shown to disrupt communication and, in high-stakes domains such as aviation and healthcare, may have critical consequences. Technology-enhanced learning, particularly through AI and gamification, demonstrates potential in fostering pragmatic competence, while culturally embedded expressions and religious idioms illustrate the importance of contextual awareness. The integration of pragmatics into teacher education and curricula emerges as essential for preparing learners to navigate intercultural interactions effectively. This review concludes that systemic reforms, policy innovations, and targeted pedagogical strategies are required to address persistent gaps in pragmatic education. Future research should examine long-term pragmatic adaptation and digital communication contexts to further advance understanding and practice. These findings emphasize the urgent need for pragmatic competence as a core dimension of intercultural communication.